Negotiating group identities in multicultural Germany : the role of mainstream media, discourse relations, and political alliances - Abadi, David (Communication, globalization, and cultural identity., 2017)
"This study provides an interdisciplinary examination of media portrayals of ethnic and religious minorities in Germany. Using years of combined quantitative and qualitative research, the author compares parliamentary discourse with that of the mainstream media and analyzes the politicized uses of collective identities."--Provided by publisher